Land reform process in Namibia: a study of the impact of land reform on beneficiaries in Otjozondjupa region, Namibia - Geingob, Phillipus (University of the Western Cape, 2013)
Masters in Public Administration - MPA === The Government of Namibia has been responsible for facilitating the resettlement of destitute and landless people since its independence in 1990. The provision of resettlement is a very contentious issue in Namibia. The bulk of land is still in the hands of minority white communities and foreigners. It is against this background that the study examined the land reform process in Namibia. The objectives of the study was to investigate to what extent the land reform process has been successful in one of Namibia's regions, and what factors are relevant for success, and identify ways to improve the process; to examine the original government objective/policy and how/why it changed over time. === South Africa